Mental health and diabetes self-management: assessing stakeholder perspectives from health centers in Northern Mexico - Benjamín Aceves; Manuel Ruiz; Maia Ingram; Catalina Denman; David O. Garcia; Purnima Madhivanan; Cecilia Rosales (BMC, 2021)
Abstract Background People living with diabetes have an increased risk of developing mental health issues. Mexico has observed a high prevalence of people living with diabetes suffering from mental health issues, such as anxiety and depression. Self-management programs have demonstrated promise in helping participants address and prevent not only physiological health complications but mental health issues as well. This qualitative study aimed to understand the mental health benefits of a diabetes self-management intervention for health centers in Northern Mexico and opportunities for improvement through assessing stakeholder perspectives. Methods Trained research staff used a semi-structured questionnaire guide to conduct all interviews and focus groups from February-May 2018. Individual interviews (n = 16) were conducted face-to-face at four health center sites among all health center directors and key staff located throughout the state of Sonora. One focus group (n = 41) was conducted at each of the four health centers among intervention participants. Directed content analysis was used to establish themes by understanding relationships, identifying similar experiences, and determining patterns across datasets. Results In total 57 health center directors, health center staff, and intervention participants were involved in the interviews and focus groups across the four health centers. Overall the analysis identified four themes throughout the data, two were categorized as benefits and two as improvements. The primary themes for participant benefits were an increase in self-efficacy and social support to manage their chronic conditions. These were evident from not only participant perspectives, but health staff observations. Conversely, increased family involvement, and increased mental health integration and services within diabetes care were identified themes for opportunities to improve the intervention to be more inclusive and holistic. Conclusion All stakeholders observed the benefits for intervention participants and opportunities for more inclusivity of the family and integration as well as an increase in mental health services. The themes identified demonstrated a need to more proactively enhance and utilize diabetes self-management as a means to improve mental health outcomes among people living with diabetes in Mexico. This is an opportunity to employ a more comprehensive approach to diabetes self-management, and integrate mental health services into overall diabetes care. Trial registration www.ClinicalTrials.gov, identifier: NCT02804698 . Registered on June 17, 2016.